Indonesian School Students’ Knowledge After Online Dental Health Education: A Scoping Review - Caesary Cloudya Panjaitan; Nisa Ikhlasul Amalya (Indonesian Dental Association, 2025)
One way to prevent dental health problems is through Dental Health Education (DHE). Elementary, junior, and senior high school students are ideal participants for DHE, and it is expected that their knowledge will increase after receiving DHE. During the COVID-19 pandemic, DHE has adapted its traditional offline to online method using various educational media. This review aimed to identify the theoretical overview presented in the literature regarding Indonesian school students' knowledge after online DHE. Article searches by Google Scholar database and focusing on students' knowledge after online DHE. Selected articles were screened and structurally read by two persons. In this research, 853 articles identified. Subsequently, articles filtered and presented in a data extraction table with three categories: elementary, junior, and senior high school. There were 30 included articles: elementary school (n=18), junior high school (n=9), and senior high school students (n=3). In each inclusion article, the students' knowledge increased after online DHE, as evidenced by the rise in mean scores from pretest to posttest with significant test (p<0.05), if present. Dental health education media varied by level: elementary school = educational video, junior high school = Zoom Meetings, and senior high school = Instagram. In conclusion, the students' knowledge after online dental health education has increased through various media.